Modern Practice of Artificial Reforestation in the Taiga Zone of the European Part of Russia - Ilintsev, Aleksey S.; Bogdanov, Aleksandr P.; Romanov, Evgeniy M.; Voronin, Vasiliy V. (Izvestiâ vysših učebnyh zavedenij. Lesnoj žurnal, 2024)
The article presents an analysis of technologies and techniques for creating forest plantations used in the Arkhangelsk and Kirov Regions, as well as the Komi Republic, based on the materials of reforestation projects for 2020. The territories under consideration belong to 6 forest areas: the Northern taiga, the Dvina-Vychegda taiga, the Southern taiga, the coniferous- broad-leafed (mixed) forests, the Western Ural taiga and the area of tundra forests and sparse taiga. The database created on the basis of the data from reforestation projects includes 13 indicators: categories of reforestation areas, forest vegetation conditions (terrain, soil type, soil moisture, group of forest types, degree of turfing), as well as tillage methods, mechanisms and aggregates used for tillage and planting seedlings and saplings and planting stock type. It has been established that in the studied regions, reforestation is more often carried out in fresh (1–2-year-old) felling areas in place of spruce plantations of blueberry forests, with podzolic drained and poorly drained soils. When cultivating soil for forest plantations, excavators are widely used (44 %), replacing traditional tractors with ploughs (usually PL-1). In most areas, furrow tillage is prevalent (52 %), but strips, mounds and patch scarification are also common (40 %). Containerized spruce and pine planting stocks have become more widely used (more than 50 % of the area), though seedlings are extremely rare (7 % in the Kirov Region). The data obtained allow us to asses the real picture of the use of reforestation technologies in the taiga zone on the example of three subjects of the Russian Federation, which will help the subjects of the Russian Federation in making management decisions for exercising their powers in the reforestation field.